The purpose of Romans. - Jervis, L. Ann (Library of New Testament studies., 1991)
This book analyses the structure and content of the four epistolary sections of a Pauline letter most directly related to the question of purpose: the opening formula, the thanksgiving, the apostolic ''Parousia'' and the conclusion. Jervis proposes that while the concerns of the letter involve Paul''s missionary plans and his desire to establish himself as the Roman Christians'' leader in the faith, the primary function of Romans is for Paul to make available to Christians at Rome the good news in all of its power. Romans is written to fulfil Paul''s mandate to establish and nurture his Roman.